Minimizing the Bullwhip Effect for Supply Chains Single Vendor and Multi Distributor in Salt Companies - Kurniasari, Fadillah; Pulansari, Farida (Image : Jurnal Riset Manajemen, 2024)
In a competitive market, companies anticipate demand and ensure product availability. However, demand uncertainty due to the bullwhip effect can disrupt a company's efforts to make proper plans. This research aims to reduce the value of the bullwhip effect to produce optimal inventory using the Vendor Managed Inventory (VMI) method in salt processing companies. This research uses a VMI method with a probabilistic inventory control model approach. So, the vendor determines the number of orders per period. The data type used is secondary data for each distributor and vendor from March 2023 to February 2024. The novelty of this research is the addition of product shortage cost variables, and research was carried out on distributors and vendors. The research results show that the VMI method can reduce the bullwhip effect on vendors by 71%, as well as in each distributor region, such as East Java by 71%, Central Java by 59%, West Java by 57%, Sulawesi by 67%, Sumatra by 62%, Kalimantan by 60%, NTB by 61%, and Bangka Belitung by 63%. This research helps companies effectively estimate optimal inventory for each distributor to avoid information distortion that will cause a bullwhip effect.